PENGENDALIAN PEREDARAN GELAP NARKOTIKA OLEH NARAPIDANA DARI DALAM LEMBAGA PEMASYARAKATAN (LAPAS) - I Gede Artha; I Wayan Wiryawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Drug smuggling by high and sophisticated operation mode recently was able reach theprisoner which is as society prison status. Law enforcement officer especially the police inconducted their function as law enforcement to the prisoner that involved in drug smuggling,in disclosure and sttlement their case (investigation step) did not easy because the prisonerwas a society in prison encironment. There are two problem in this research : 1. why theconected and correlated of the legal system for drug ? 2. Why the drug smuggling is highoperation by the prisoner which is as society prison status and to up from in the prison ?The result of this research show that the law enforcement to the doer drug smuggling bythe law enforcer. Should faced ethic code profesion society, there for it was impossible forthe law the optimize of law enforcement by law enforcer to the doer of drug smuggling inprisoner society such as intern and extern efforts, where the intern effort include increasethe coordination function and cooperation between the law enforcement especially with theprison officers.